56 Immersion deaths of indigenous peoples in Canada – epidemiology, culture, prevention. (1st September 2016) - Dalke, Shelley; Barss, Peter; Olsen, Karlyn; Hamilton, Jane
Abstract : Background: Indigenous peoples in Canada live in a mix of rural and urban areas. Open bodies of water are often essential for subsistence and recreational transport, fishing, and hunting. Death rates are several times higher than nationally. The goal is preventing immersion deaths by implementing evidence-based interventions for main activities and risk factors in culturally appropriate programs. Methods: Annual Red Cross collection of 1991–2010 coroner data by structured questionnaire, including activity, purpose, personal, equipment, environment factors, and trends. Cultural factors pertinent to interventions were assessed by literature reviews, including anthropological surveys. Interventions were developed based upon risk factors for main activities, cultural values, and practical considerations. Logistic regression was used to assess flotation device wearing, controlling for other variables. Results: Surveillance identified 1213 immersion and 27 trauma deaths. Boating, including transport, fishing, and hunting, accounted for 37% (n = 444), non-aquatic activities such as walking or playing near water and on ice 21%, aquatic such as swimming or wading 17%, land ice and air transport 17%, bathing 3%, unknown 6%. 52% involved recreation, 34% daily life/subsistence, occupational 4%, rescue 2%, other 1%, unknown 8%. Main risk groups were males ≥15 years, 73%, and 1–4 -year-olds, 9%. Swimming ability was reported for 26% of ≥5 years, including 23% non-swimmers, 12% weak, 45% average/intermediate/unspecified, 6% strong. Among ≥15 year-olds, alcohol was involved for ≥60% and illegal drugs ≥10%. Rivers and current were a factor for 35%. For 0–9-year-olds, 73% died without adults. Death rates were similar across Canada, much higher in the North. Boating death rates fell from 4.9 to 1.2/100, 000/population/year between 1991–1995 and 2006–2010; for other activities, deaths fell during 1991–2000, but not 2001–2010. Main risks for boating included non-wearing of flotation, with only 5% wearing; for 40% none was aboard. Logistic regression showed 68% (p = 0.000) reduced odds of properly wearing flotation, compared with non-indigernous. Among 0–14-year-olds, 44% of known ethnicity were indigenous, 0% wearing, others 33% wearing; no indigenous youth wore PFDs, others 13%. Capsizing, falling overboard, and swamping accounted for 75%. Waves, wind, cold water and other cold factors were frequent. For aquatic activities, 15–40-year-old males were main victims, for non-aquatic 1–4-year-olds and ≥15 males. Rivers were the most frequent body of water. Ice transport victims were predominantly ≥ 20-year-old males using snowmobiles, while both males and females ≥ 15 were victims of on-road into water deaths. Ice transport deaths mainly occurred in central and Prairie Provinces and northern territories. Most road transport immersions were in the Prairies. Conclusions: To avert immersions for all water-related activities, surveillance supports raising ability to swim and to survive in currents, especially for males, and reducing alcohol and illegal drug consumption among adult males. For children, especially 1-4-year-olds, constant adult supervision by families, and/or development of community nurseries, are essential. Internationally, mandatory flotation wearing is the most effective boating intervention. During boating and snowmobile travel on ice, wearing of flotation at all times is essential It is encouraged by programs, which need reinforcement by legislation. Cold-protective clothing is frequently essential. Culturally sensitive safety promotion is being implemented and assessed for main activities and risk groups.